2011
DOI: 10.1186/cc10120
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of high-dose oral vitamin D3 in critically ill vitamin D deficient patients: a randomized, double-blind, placebo-controlled pilot study

Abstract: IntroductionVitamin D deficiency is encountered frequently in critically ill patients and might be harmful. Current nutrition guidelines recommend very low vitamin D doses. The objective of this trial was to evaluate the safety and efficacy of a single oral high-dose vitamin D3 supplementation in an intensive care setting over a one-week observation period.MethodsThis was a randomized, double-blind, placebo-controlled pilot study in a medical ICU at a tertiary care university center in Graz, Austria. Twenty-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 29 publications
5
140
2
9
Order By: Relevance
“…One study reported that higher physiological testosterone levels in older men and women may protect against falls, and that the benefit may be additive in those taking vitamin D supplementation [35]. In critically ill patients, a single oral ultrahigh dose of 540,000 IU cholecalciferol corrected vitamin D deficiency within 2 days without causing hypercalcemia [36]. Because vitamin D and testosterone replacement are relatively inexpensive and could improve symptoms, function, and quality of life, prospective intervention studies in patients with cancer are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that higher physiological testosterone levels in older men and women may protect against falls, and that the benefit may be additive in those taking vitamin D supplementation [35]. In critically ill patients, a single oral ultrahigh dose of 540,000 IU cholecalciferol corrected vitamin D deficiency within 2 days without causing hypercalcemia [36]. Because vitamin D and testosterone replacement are relatively inexpensive and could improve symptoms, function, and quality of life, prospective intervention studies in patients with cancer are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, we knew that all patients with low vitamin D level had received vitamin D as a single loading dose of 600,000 IU in this study. It has been demonstrated that vitamin D deficiency can be corrected with the same dose of enteral vitamin D replacement in critically ill patients (25,26). In our study, patients with vitamin D level <25 ng mL -1 at ICU admission had a median vitamin D level after vitamin D replacement of 31.6 ng mL -1 .…”
Section: Discussionmentioning
confidence: 61%
“…Probably this was due to a substrate boost for local tissue mitochondrial 1-alpha-hydroxylase activity. There were large individual differences in 25(OH)D3 levels probably due to large variations in gastrointestinal absorption [51]. Intravenous formulations could overcome this problem but i.v administration of calcitriol had no impact on 25(OH)D3 and 1.25 di-(OH)D3 levels in septic patients as shown in the Mata-Granados study [28].…”
Section: Vitamin D Supplementationmentioning
confidence: 93%